Integrating game-based approach in students learning experiences in physical education: A phenomenological study - Culajara, Carla Jobelle (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
In the transition to the delivery of instruction, game-based learning in physical education is the key to filling the instructional gap by giving each student the freedom to develop their skills in the 21st century. This study employed a qualitative research design using a phenomenological approach to acquire an in-depth understanding of students' learning experiences through game-based learning in Physical Education. Participants were chosen through purposive sampling which was participated by 7 students from the Grade 10 level in one of the secondary public schools in the Philippines. Codes and themes were transcribed in the study. Based on the research results, three themes emerged: innovative approach, the functionality of the application, and student engagement and authentic learning experience. Physical education teachers have become innovative and creative in how to deliver instruction, especially in the areas of cognitive and skills acquisition using a game-based approach. This is done to help all students to be creative and adapt to the modern learning environment. This application was practical, usable and accessible for every student both inside and outside of the classroom with offline and online features. This study will equip Physical Education teachers with clarity and a road map to the modern world. This will also provide the required support for students to shift away from traditional classroom learning and become more innovative by producing mobile apps that provide students with games and the freedom to absorb the lesson through a game-based approach.